Nitriding of commercial pure titanium in the plasma of frequency-pulsed non-selfsustained glow discharge with a hollow cathode at low pressure; High Temperature Material Processes: An International Quarterly of High-Technology Plasma Processes; Vol. 21, iss. 1 - Fedorovich Yu. F. Yury Fedorovich; Laskovnev A. P.; Denisov V. V. Vladimir Viktorovich; Uglov V. V. Vladimir Vasilievich; Petrikova E. A. Elizaveta Alekseevna; Krysina O. A.; Shymanski V. I.; Cherenda N. N. Nikolay Nikolaevich; Koval N. N. Nikolay Nikolaevich (2017, 2017)
Title screen